Loss rates of Europa׳s tenuous atmosphere. (1st October 2016) - Lucchetti, Alice; Plainaki, Christina; Cremonese, Gabriele; Milillo, Anna; Cassidy, Timothy; Jia, Xianzhe; Shematovich, Valery
Abstract: Loss processes in Europa's tenuous atmosphere are dominated by plasma–neutral interactions. Based on the updated data of the plasma conditions in the vicinity of Europa (Bagenal et al. 2015 ), we provide estimations of the atmosphere loss rates for the H2 O, O2 and H2 populations. Due to the high variability of the plasma proprieties, we perform our investigation for three sample plasma environment cases identified by Bagenal et al. as hot/low density, cold/high density, and an intermediate case. The role of charge-exchange interactions between atmospheric neutrals and three different plasma populations, i.e. magnetospheric, pickup, and ionospheric ions, is examined in detail. Our assumptions related to the pickup and to the ionospheric populations are based on the model bySittler et al. (2013) . We find that O2 –O2 + charge-exchange is the fastest loss process for the most abundant atmospheric species O2, though this loss process has been neglected in previous atmospheric models. Using both the revised O2 column density obtained from the EGEON model (Plainaki et al., 2013 ) and the current loss rate estimates, we find that the upper limit for the volume integrated loss rate due to O2 –O2 + charge exchange is in the range (13–51)×10 26 s −1, depending on the moon׳s orbital phase and illumination conditions. The results of the current study are relevant to the investigation of Europa's interaction with Jupiter׳s magnetospheric plasma. Highlights: Loss rates depend on highly variable plasma conditions The cold plasma electron population is the mainly responsible for H2 O and H2 loss Maximum loss is expected under median and median or high plasma conditions for H2 O and H2 respectively O2 –O2 + charge-exchange process may have a dominant role in the exosphere loss O2 –O2 + charge transfer rate is in the range (13–51)×10 26 s −1